The State accounts certification in the core of the modernization of public management - ELARABI , Fatima ezzahra; BENREZZOUQ , Noura (Revue Internationale du Chercheur, 2023)
In a context of public management modernization, and research for performance transparency and financial information sincerity, Morocco has, with the passage of the finance organic law n°130.13 (LOF 2015), launched in a reform of public accounting, moving from a cash accounting limited to a budget accounting to a three-dimensional accounting system adding to it both general accounting and cost-analytic accounting. For this purpose, the LOF 2015 granted to the Court of Auditors the mission to certify State accounts in order to devote the principle of accounts sincerity and improve the reliability and transparency of State accounts. This Article is looking to demonstrate the role of this new mission of accounts certification in the process of public management modernization, and, above all, to understand what the accounts certification is, and why is that? as well as the preconditions to succeed this mission.